Positioning Medical Assistants for a Greater Role in the Era of Health Reform. (October 2015) - Chapman, Susan A.; Marks, Angela; Dower, Catherine
Abstract : Medical assistants (MAs) are one of the fastest-growing occupations in the United States. As of 2014 there were about 585, 000 MAs in the United States, and the Bureau of Labor Statistics projected the MA workforce to grow by 29% from 2012 to 2022. The MA population is primarily female, ethnically and racially diverse, and paid about $15.01 per hour. MAs are primarily educated in private schools, many at for-profit institutions. The MA curriculum and length of training can be quite varied and can lead to uneven preparation for practice. Traditionally, the MA role has involved a limited clinical role and little involvement with team care, particularly in larger practices or clinics. Medical groups, clinics, and health systems are now taking a new look at MAs and how they can play a greater role in reforming health care delivery models. Expanded roles for MAs might include health coach, referral coordinator, disease registry manager, and health screener using protocols. In expanding MA roles, education and regulatory issues need to be addressed by the provider community including current inconsistent regulation and certification requirements and the lack of preparation for expanded roles in traditional MA training programs. MAs are well positioned to help address challenges in the health care delivery system including improving access to care while reducing overall cost. Successful model practices using MAs in expanded roles need further formal evaluation and replication across practice settings.